PENGARUH ORIENTASI PASAR TERHADAP KEPUASAN PELANGGAN PT HADJI KALLA DI KOTA PALU - Apriyono, Tri (Jurnal Minds: Manajemen Ide dan Inspirasi, 2015)
The aims of this research are : (1) To identify and analysis simultaneously the influence of the dimensions of market orientation on customer satisfaction PT Hadji Kalla in Palu, (2) To identify and analysis the partial effect of market orientation dimensions on customer satisfaction PT Hadji Kalla in Palu. This study uses primary data through a survey on 100 people customers who never buy or buy back at PT Toyota products. PT. Hadji Kalla in town Palu. survey conducted in April s.d June 2013. Data were analyzed using SPSS for Windows program and Excel 2010. This study uses primary data through a survey of 100 people customers who never buy or buy back at products Toyota PT Hadji Kalla in town Palu. survey conducted in April s.d July 2013. Data were analysis using program SPSS for Windows 11. The results showed that: (1) the dimensions of market orientation consists of customer orientation, competitor orientation and coordination among functions simultaneously have a positive and significant effect on customer satisfaction: (2) dimensions of market orientation consists of customer orientation, competitor orientation and coordination among partial functions or a significant positive effect on customer satisfaction. This means that companies that adopt a market orientation will enjoy the financial assessment of the quality and superior execution. The company's ability to generate superior services, as it allows a better understanding of the needs of the target market. Understanding the needs of the target customers allows the company to coordinate all of the assets, and also allows the company to increase the value for customers.